Policy Workshop on Co-learning Opportunity for the Water, Energy, Food and Ecosystems (WEFE) Nexus in Nepal - Adhikari, Manju; Baral, Sanjeeb; Nepal, Santosh (International Water Management Institute, 2022)
Within Nepal, water, energy, food, and ecosystems (WEFE) are vital resources not merely for the current generation, but also for future ones, especially to satisfy the demands of a growing population and to respond to socio-economic changes. The WEFE nexus approach realizes that the management of water, energy, food, and ecosystems must be undertaken in a holistic way. Nevertheless, governments, investors, and other stakeholders face challenges in the management of WEFE resources, particularly in the face of climate change. Notably, a lack of coordination in utilizing such resources can be a source of potential conflict in many areas. On June 19 and 20, 2022, the International Water Management Institute (IWMI) and the Department of Water Resources and Irrigation (DWRI) co-organized a co-learning workshop to discuss the challenges and opportunities of integrated management of WEFE resources using the nexus thinking approach in Nepal.